Novel Multidisciplinary Management of Acute Kidney Injury After Infant Orthotopic Heart Transplantation. Issue 3 (May 2020) - Wang, Billy C.; Gordon, Brent M.; Chau, Peter; Martens, Timothy P.; Lion, Richard P.
Acute kidney injury following orthotopic heart transplantation in pediatric recipients is often multifactorial, requiring balance of immune suppression, nephrotoxic medication exposure, nutrition, and fluid status. Therapeutic options are often limited by patient size and hemodynamic stability. We describe a four-month, 4.9-kg female bridged by mechanical circulatory support to transplant after failed stage 1 palliation secondary to recurrent aortic stenosis and severe ventricular dysfunction. Posttransplant, kidney injury was managed by transcatheter relief of central obstruction from an anastomotic stricture and continuous renal replacement therapy, allowing uninterrupted immune suppression, medication, and nutrition delivery until sufficient recovery of renal function.